Niosomes: Best Approach for Novel Drug Delivery and Future Aspects - Gandhimathi, R. (Asian Journal of Pharmaceutics (AJP), 2024)
When hydrated with synthetic non-ionic surfactants, niosomes-vesicles of non-ionic surfactants-are formed, either with or without the inclusion of cholesterol or other lipids. Niosomes are effective and non-ionic for the distribution of drugs; it is less harmful and increases the drug therapeutic index by limiting its impact to target cells. Niosomes gain growing scientific attention in nanotechnology because they are exceptional in their versatility as valuable drug delivery mechanisms for a range of therapeutic applications. Niosomes were prepared by various methods like sonication, microfluidization, the handshaking approach, reverse-phase evaporation, and the ether injection method. Two separate conditions, commonly 4±1° and 25±2°, are used for storing niosomes. Niosomes have various applications in neoplasia, Leishmaniasis, peptide drug delivery, and immunological disorders.